2015
DOI: 10.17576/jsm-2015-4401-13
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metal in Self-caught Saltwater Fish from Port Dickson Coastal Water, Malaysia

Abstract: Freshwater fish has been studied and reported numerously. However, little attention has been made and limited studies available on local marine fish in Malaysia. Thus, in 096 mg/kg bagi Cd, 1,34 mg/kg bagi Cr, 8,44 mg/kg bagi Pb dan 1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The THQ for adults and children was also below 1.00. A study by Praveena and Lin [89], revealed that the THQ values calculated for Cu in marine fish collected from Port Dickson (west coast of Peninsular Malaysia) were also less than one, indicating that there were no Cu adverse effects via fish consumption.…”
Section: Health Risk Assessment Of Cumentioning
confidence: 99%
“…The THQ for adults and children was also below 1.00. A study by Praveena and Lin [89], revealed that the THQ values calculated for Cu in marine fish collected from Port Dickson (west coast of Peninsular Malaysia) were also less than one, indicating that there were no Cu adverse effects via fish consumption.…”
Section: Health Risk Assessment Of Cumentioning
confidence: 99%
“…Children and adults had THQs below 1.00. Praveena and Lin [89] Cu THQ levels were below 1 in all 40 commercial fish species (Figure 3) and selected fish species' skin portions (Figure 4), indicating low non-carcinogenic risk and safe human intake. The absence of Cu health risks was also established.…”
Section: Cu Health Risk Assessmentmentioning
confidence: 99%
“…Children and adults had THQs below 1.00. Praveena and Lin [89] observed that marine fishes from Port Dickson (west coast of Peninsular Malaysia) had Cu THQ values below 1, suggesting no Cu adverse effects from eating. According to Table 1 and Figure 5, Cu EWI ranged from 0.10 to 27.3 µg/kg BW/we with Arius arius and Tylosurus crocodilus having the lowest and greatest concentratio Figures 5 and 6 show reduced EWI in 40 fish species' dorsal muscles and 10 fish spec skin parts compared to the Cu (3500 µg/kg BW/week) determined PTWI.…”
Section: Cu Health Risk Assessmentmentioning
confidence: 99%
“…Subsequently, heavy metals that are released to the aquatic environment can bioaccumulate along the aquatic food chain (11), with prolonged and continuous consumption of contaminated aquatic organisms posing a significant health risk to the community (12). In fact, even in small amounts, heavy metals can either in the body or in a metabolically available form that affects essential biochemical processes (13).…”
Section: Introductionmentioning
confidence: 99%